2007
DOI: 10.1029/2006jd008352
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus optical properties observed with lidar, radiosonde, and satellite over the tropical Indian Ocean during the aerosol‐polluted northeast and clean maritime southwest monsoon

Abstract: [1] Cirrus formation and geometrical and optical properties of tropical cirrus as a function of height and temperature are studied on the basis of INDOEX (Indian Ocean Experiment) lidar and radiosonde measurements and satellite observations of deep convection causing the generation of anvil cirrus. Lidar and radiosonde measurements were conducted at Hulule (4.1°N, 73.3°E), Maldives, during four field campaigns carried out in FebruaryMarch 1999 and March 2000 (northeast (NE) monsoon season, characterized by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 60 publications
(122 reference statements)
13
95
1
4
Order By: Relevance
“…This model has been compared to Eloranta's model (Eloranta, 1998) for a wide range of cloud profiles and lidar parameters and found that reproduces the high-order Eloranta calculation when the latter takes into account 5th or 6th order scattering (Hogan, 2006). This model was also used by Seifert et al (2007) to estimate the contribution of multiple scattering effects to the effective optical properties of cirrus clouds during Indian Ocean Experiment (INDOEX). A laser beam of 0.5 mrad full-angle divergence with a wavelength of 355 nm, and a receiver field of view of 1 mrad are used in the model simulation.…”
Section: Multiple Scattering Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…This model has been compared to Eloranta's model (Eloranta, 1998) for a wide range of cloud profiles and lidar parameters and found that reproduces the high-order Eloranta calculation when the latter takes into account 5th or 6th order scattering (Hogan, 2006). This model was also used by Seifert et al (2007) to estimate the contribution of multiple scattering effects to the effective optical properties of cirrus clouds during Indian Ocean Experiment (INDOEX). A laser beam of 0.5 mrad full-angle divergence with a wavelength of 355 nm, and a receiver field of view of 1 mrad are used in the model simulation.…”
Section: Multiple Scattering Effectmentioning
confidence: 99%
“…Cirrus climatological results from Observatoire de haute Provence in France are presented by Goldfarb et al (2001) and suggest as more prevalent optical depth in the region from 0.03 to 0.1. In addition, Seifert et al (2007) have studied the optical properties of cirrus clouds over the tropical Indian ocean during Northeast (NE) and Southwest (SW) monsoon seasons. They found a multiple-scattering corrected optical depth of 0.25±0.26 (NE) and 0.34±0.29 (SW), while the lidar ratio values were found to be 33±9 sr (NE) and 29±11 sr (SW).…”
Section: Optical Properties Of Cirrus Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the 15 increase of the height, the temperatures gradually decrease. According to the previous work (Chen et al, 2002, Sunilkumar and Parameswaran, 2005, Seifert et al, 2007, He et al, 2013, temperature has great impact on linear particle depolarization ratio and extinction coefficient by dominating the crystal shape, number concentration and other microphysics properties of cirrus. Furthermore, the cloud base and top height of the first cirrus layer are 6.02  0.60 km and 8.56  0.69 km, respectively.…”
Section: Case Studymentioning
confidence: 99%
“…In this study, for accurately correcting the MS influence, we perform a full treatment of multiple scattering following the model of Hogan (2008). The model is also introduced and applied by Seifert et al (2007), Kienast-Sjögren et al (2016) and Gouveia et al (2017). In this model, the typically operated FOV of 1.3 mrad and the full divergence angle of 0.5 mrad in WACAL is input.…”
Section: Multiple Scattering Correctionmentioning
confidence: 99%